Aromatic compounds from three Brazilian Lauraceae species - de Luca Batista, Andrea Nastri (2010)
Phytochemical investigations on three Brazilian Lauraceae species from the Cerrado region of São Paulo State, Ocotea corymbosa (Meins) Mez., O. elegans Mez. and Persea pyrifolia Nees & Mart. ex Nees resulted in the isolation of favonoids, an ester of the 4-O-E-caffeoylquinic acid, an aromatic sesquiterpene besides  furofuran  lignans. This  is  the frst chemical study on  the  leaves of Ocotea elegans and O. corymbosa as well as the frst report of non-volatile compounds from Persea pyrifolia.